In Search of the Folk Daoists of North China. - Jones, Stephen (Ashgate Pub., 2010)
Largely unstudied by scholars of religion, folk Daoist ritual in north China has been a constant theme of Chinese music scholars. Stephen Jones places lay Daoists within the wider context of folk religious practices - including those of lay Buddhists, sectarians, and spirit mediums. Jones describes ritual sequences within funerals and temple fairs, offering details on occupational hereditary lay Daoists, temple-dwelling priests, and even amateur ritual groups. Stressing performance, Jones observes the changing ritual scene in this poor countryside, both since the 1980s and through all the trib.